The effect of apple (Malus Domestica) juice on the damage of mice liver cells due to paracetamol treatment - Hartanto, Anthony; Dardjan, Murnisari; Kintawati, Silvi (Padjadjaran Journal of Dentistry, 2009)
The liver is an important organ for body metabolism process. Liver disease is one of serious health problems in developing countries including Indonesia. Liver damage is caused by viral infection, toxic agent exposure (medications, alcohol), hormonal disturbance, neoplasm and autoimmune diseases. The use of high dose paracetamol to reduce pain also leads to liver damage. Apple (Malus domestica) juice is a natural anti oxidant agent. This laboratory experimental study was performed to discover the effect of giving apple juice on damaged cell regeneration due to the use of paracetamol. The study was performed in 21 male mice from Swiss-Webster strain that were divided into group I, II, and III. Group, I served as control while group II received 1 mg/ml paracetamol dose for 5 days and Group III received 1 mg/ml paracetamol for 5 days and 1 ml of apple juice on the 5th to 10th day. The observation of the mice liver cells was conducted using a light microscope with 400x magnification to get the number of necrotic liver cells per view field. The results of this study showed a difference in the number of necrotic liver cells between Group II and III. ANOVA statistical test ( = 0.05) concluded that apple juice significantly helps regeneration process in damaged liver cells caused by paracetamol.